The responses of secondary forest tree seedings to soil enrichment in Peninsular Malaysia : an experimental approach - Hashim, Nor Rasidah; M.R. Hughes, Francine (International Society for Tropical Ecology, 2010)
Secondary forests are gaining prominence in tropical landscapes, but in areas adjacent to agricultural land the mix of species found in them is likely to be influenced by high rates of fertilisation and nutrient run-off. We conducted a pot experiment on three secondary forest species, Glochidion obscurum, Lagerstroemia speciosa and Vitex pinnata, to ascertain their response to nutrient addition. We used three treatments, (1) control (no fertilizer addition); (2) addition of 1 g of rock phosphate; and (3) addition of 1 g NPK, and found that G. obscurum and L. speciosa increased their growth when levels of nitrogen, phosphorus and potassium were increased, indicating evolutionary adaptation to use a high resource strategy. However, V. pinnata did not show the same pattern. It is, therefore, possible that on-going fertilization of low-lying secondary forests will produce growing conditions that lead to the reduction of non responsive species such as V. pinnata and favour others, such as G. obscurum and L. speciosa, at least in the early stages of forest succession.